A review of Australian salt lakes and associated mineral systems. Issue 2 (17th February 2016) - Mernagh, T. P.; Bastrakov, E. N.; Jaireth, S.; de Caritat, P.; English, P. M.; Clarke, J. D. A.
ABSTRACT: This study reviews the available information for over 1200 Australian salt lakes including in areas that have little or unreliable data. Publicly available groundwater hydrogeochemical datasets for the Australian arid zone are particularly sparse, inconsistent and of variable quality. Many datasets in the vicinity of salt lakes only report salinity or total dissolved solids, with no data for constituent cations and anions, and no appreciation of the hydrological and geomorphic evolution of the lakes. To overcome these limitations and to provide a broad-scale context, we developed mineral systems models to assess the potential of Australian salt lakes for potash, lithium and boron deposits. These models show that an important control on the potential of salt lake systems to form economic deposits of potash, lithium or boron is hydrogeological connectivity between leachable source rocks and the lakes. The assessment of the mineral potential was carried out in two stages. The first stage selection was based on the presence of favourable source rocks in the salt lakes' catchments. The mean values of concentration in each catchment were derived from whole rock, sediment and groundwater geochemical datasets by averaging the values in samples (separately for each of the three datasets) located in the catchment and assigning this value to the catchment's salt lakes. The second stage selection was carried out by analysing available chemical data of groundwater in proximity to the salt lake systems delineated in the first stage. As a result, six regions were identified as having the highest potential, for potash in particular, but also for lithium and/or boron deposits. These are: the Lake Frome/Central Gawler Region of South Australia; two regions in the Northern Territory: the central western region extending into Western Australia, and the Lake Woods region; and, in Western Australia, the Lake Disappointment region, the north east Yilgarn and south east Yilgarn regions.